Modelling the impact of software components on wireless sensor network performance - Gama, Oscar (2011)
Network Simulators are often used to study multiple aspects of data communications in distinct scenarios, including wireless sensor networks (WSN). However, the performance of the software components running in the network nodes is normally neglected by the simulators. This aspect is particularly important in WSNs, as nodes have very limited computing resources. In order to study the impact of software components on WSN performance, a simulated WSN and a physical WSN were setup in the IEEE 802.15.4 domain. Tests revealed that the simulator must take into account the software components of the WSN to produce realistic results. To achieve this, new parameters are proposed to model the impact of the software components on a physical WSN. Tests measuring the packet round-trip delay, delivery error ratio, and duplicated packet ratio showed that the inclusion of this model in a simulator improves significantly the accuracy of the results when compared with those obtained in a physical WSN.